2013
DOI: 10.1016/j.ygeno.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TP53, CTNNB1 and PIK3CA genes in hepatocellular carcinoma associated with hepatitis B and hepatitis C virus infections

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer death worldwide. Hepatocarcinogenesis is a multistep process mainly associated with persistent infection with hepatitis B (HBV) or C (HCV) viruses and always involving the accumulation of genetic alterations over decades of chronic liver disease. Mutations in TP53 and CTNNB1 genes are considered the cancer drivers for HCC development with variable frequencies depending on the etiology. Here we present a comprehensive review evaluating somatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 106 publications
7
113
1
1
Order By: Relevance
“…Somatic and inherited mutations in APC leading to prematurely truncated protein are most frequently found in colorectal cancers (49). Mutations in b-catenin altering or deleting the GSK3 phosphorylation sites (Ser33, Ser37, and Thr41) are reported in various cancers, including pancreatic, gastric, liver, and endometrial cancers (64). These mutations prevent b-catenin degradation, leading to enhanced LEF/TCF-mediated transcription.…”
Section: Mutations That May Sensitize Cancer Cells To Secreted Wnt LImentioning
confidence: 99%
“…Somatic and inherited mutations in APC leading to prematurely truncated protein are most frequently found in colorectal cancers (49). Mutations in b-catenin altering or deleting the GSK3 phosphorylation sites (Ser33, Ser37, and Thr41) are reported in various cancers, including pancreatic, gastric, liver, and endometrial cancers (64). These mutations prevent b-catenin degradation, leading to enhanced LEF/TCF-mediated transcription.…”
Section: Mutations That May Sensitize Cancer Cells To Secreted Wnt LImentioning
confidence: 99%
“…Four-parameter logistic model was applied to calculate IC 50 . The two-tailed Student t test was applied for paired data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Over 50% of human aflatoxininduced HCC harbor G249T mutation (47), while non-aflatoxin-induced, HBV-related and HCV-induced HCC have low mutation rate (48,49). More importantly, deletion of p53 is rare in human HCC (50). Therefore, Rubone is a suitable agent to treat HCC that retains p53 in cancer cells.…”
Section: Mir34a Modulator Inhibited Proliferation and Induced Apoptosmentioning
confidence: 99%
“…In countries where HCV infection is endemic (Japan or some areas of Southern Italy), a high prevalence of HCV infection has been reported among people with HCC [14,15]. Several studies found a three-fold increase in HCV-related HCC, whereas the rate of HCC associated with HBV or alcohol-induced liver disease and idiopathic cirrhosis remained stable [2,16].…”
Section: Introductionmentioning
confidence: 99%